Gateways and climate: The Drake Passage opening - Lodolo, Emanuele (2010)
The Oligocene opening of the Drake Passage between the southern tip of South America and the Antarctic Peninsula, and the subsequent evolution of the Scotia plate, have definitively separated Antarctica from the other continental masses, and have created conditions for the development of the Antarctic Circumpolar Current. This annular water flow has had a profound influence on the global climate system because it has allowed the free transfer of water masses between the Pacific and Atlantic Oceans at mid to high southerly latitudes. The comparative seismic analysis of the passive margins of the western sector of the Scotia plate, represented by the Tierra del Fuego continental margin to the north, and by the Terror Rise to the south, has shown significant morphological and structural similarities between these two margins, supporting the interpretation that they were conjugate before the Drake Passage opened. Moreover, the identification of the oldest magnetic anomalies present at the base of the two margin pairs, corresponding to about 32 million years ago, has allowed the reconstruction, through time, of the relative positions of the two continental margins, and to constrain the events that occurred immediately after the break-up and opening of the Drake Passage. These timings correlate with events seen in the oxygen isotope record from benthic foraminera, and support the view that the Drake Passage opening was the trigger for abrupt Eocene-Oligocene climate deterioration and the growth of extensive ice sheets on the Antarctic continent.